The shear mechanical properties of rocks with variable angle joints - Guoyong Duan; Yuchen Zhou; Fei Li; Yanhai Wang (Scientific Reports)
Abstract Variable angle structural surfaces are more common in slopes. However, variable-angle joints have still been approximated as single-angle straight joint planes for analysis in previous studies, which failed to comprehensively capture the mechanical properties of such surfaces. In this paper, joint specimens with variable angles were fabricated using concrete. Direct shear tests were carried out under different normal stress conditions, and the strength, deformation, and failure characteristics of the specimens were analyzed. The results revealed a significant positive correlation between the peak shear strength and shear stiffness of the variable angle specimens with the normal stress, while the correlation between the residual shear strength and the normal stress was relatively insignificant. The normal displacement and tangential displacement of the specimen exhibited a significant negative correlation. When shear failure occurred, the main cracks propagated along the shear direction, accompanied by localized secondary cracks and surface spalling. Unlike the straight joints commonly studied in previous research, variable-angle joint specimens exhibit distinct failure modes in the high-angle zone and the low-angle zone. In the high-angle zone, vertical cracks perpendicular to the joint surface and shear cracks along the shear direction predominantly occurred. The low-angle zone was dominated by shear damage along the shear direction. By comparing the results of experimental tests and theoretical analysis, the zonal pattern of shear failure characteristics on variable angle surfaces was revealed. The research findings provide a theoretical basis for the safety and stability analysis of variable angle structural surfaces.